2016
DOI: 10.1016/j.childyouth.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence on legal levers aimed at addressing child maltreatment

Abstract: a b s t r a c t a r t i c l e i n f oLaw is a powerful tool for combatting public health issues. This article reviews existing empirical research on the effect of eight legal levers on outcomes related to child maltreatment. Laws created with the intent to address child maltreatment are often enacted without empirical basis. Further, following implementation, there is little empirical research on whether such statutes reduce or deter child maltreatment and improve child outcomes. This is in part due to the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Lloyd (2015) and Zhang, Huang, Wu, Li, and Liu (2019) provide the most methodologically robust reviews, yet these reviews still either only focus on child outcomes or the synthesis only includes studies that reported statistically significant outcomes (Lloyd, 2015) or a restricted timeframe (Zhang et al, 2019). While Wittouck et al (2013) and Eldred and Gifford (2016) include some studies with parent-level outcomes, their reviews are subject to bias by only searching one database (Wittouck et al, 2013) or excluding research not published in peer-review outlets (Eldred & Gifford, 2016).…”
Section: Why It Is Important To Do the Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Lloyd (2015) and Zhang, Huang, Wu, Li, and Liu (2019) provide the most methodologically robust reviews, yet these reviews still either only focus on child outcomes or the synthesis only includes studies that reported statistically significant outcomes (Lloyd, 2015) or a restricted timeframe (Zhang et al, 2019). While Wittouck et al (2013) and Eldred and Gifford (2016) include some studies with parent-level outcomes, their reviews are subject to bias by only searching one database (Wittouck et al, 2013) or excluding research not published in peer-review outlets (Eldred & Gifford, 2016).…”
Section: Why It Is Important To Do the Reviewmentioning
confidence: 99%
“…Wittouck, Dekkers, De Ruyver, Vanderplasschen, and Vander Laenen ( 2013 ) aimed to synthesize existing evidence for drug treatment courts on substance use more generally and provide a qualitative synthesis that includes FTDC studies. Eldred and Gifford ( 2016 ) used systematic search and screening to identify peer‐reviewed US research that examines the use of legal approaches for addressing child maltreatment. The authors provide a brief narrative synthesis with cites to some existing FTDC evaluation studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… One review examines the impact of home‐visiting interventions during pregnancy and the postnatal period for women with substance misuse issues and their impact across a range of parental and child outcomes (Turnbull & Osborn, 2012 ). Three reviews focus on Family Treatment Drug Courts for substance misusing parents with and their impact on child out‐of‐home placement (Llyod, 2015), child welfare system outcomes (Zhang, Huang, Wu, Li, & Liu, 2019 ) or child maltreatment outcomes (Eldred & Gifford, 2016 ). One review examines the impact of multidimensional interventions for substance misusing mothers and their impact on multiple child outcomes (Niccols et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three reviews focus on Family Treatment Drug Courts for substance misusing parents with and their impact on child out‐of‐home placement (Llyod, 2015), child welfare system outcomes (Zhang, Huang, Wu, Li, & Liu, 2019 ) or child maltreatment outcomes (Eldred & Gifford, 2016 ).…”
Section: Introductionmentioning
confidence: 99%